The clinical significance of neutrophil-lymphocyte ratio in patients treated with hemodialysis complicated with lung infection. Issue 29 (23rd July 2021) - Li, Ling-Lin; Yang, Yu-Qiong; Qiu, Min; Wang, Li; Yuan, Hong-Ling; Zou, Ren-Chao
Abstract : Abstract: The goal of this work was to investigate the potential significance of neutrophil-lymphocyte ratio (NLR) in patients treated with maintenance hemodialysis (MHD). Herein, we retrospectively reviewed the electronic medical records of 100 patients with end-stage renal failure who were treated with MHD. All patients enrolled in this study met the inclusion criteria and were followed. The differences in each indicator between the two groups were compared using the Wilcoxon rank-sum test. On the other hand, Spearman correlation and logistic regression analysis were used to explore the correlation and risk factors for pulmonary infection between NLR and other indicators. Finally, we determined the optimal cut-off values for NLR, hypersensitive c-reactive protein (hs-CRP), and procalcitonin (PCT) diagnosis of pulmonary infection using the receiver operating characteristic curve. We found that NLR was positively correlated with age, PCT, hs-CRP, and hospital stay, but negatively correlated with hemoglobin, red blood cell, and Albumin. The expression levels of PCT, hs-CRP, and NLR in the infected group decreased significantly than those before treatment. Multiple regression analysis revealed that NLR is an important independent risk factor for MHD patients with pulmonary infection. Additionally, receiver operating characteristic curve analysis showed that the sensitivity, specificity, and area under the curve were 87.76%, 100%, and 0.920 when using NLR combined with hs-CRP to predict pulmonary infection in MHD patients, whereas that of NLR combined with PCT were 87.76%, 96.08%, and 0.944, respectively. Findings from this study suggested that NLR is an independent risk factor for MHD patients with pulmonary infection, which can effectively predict pulmonary infection. Moreover, sensitivity and specificity were greatly enhanced when using NLR combined with PCT/hs-CRP to predict pulmonary infection in MHD patients. Abstract : Supplemental Digital Content is available in the text